2013
DOI: 10.2967/jnumed.112.110148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 18F-Choline PET/CT in Prostate Cancer Patients with Biochemical Recurrence: Influence of Androgen Deprivation Therapy and Correlation with PSA Kinetics

Abstract: We evaluated the potential of 18 F-fluoromethyldimethyl-2-hydroxyethyl-ammonium (FCH) PET/CT in the detection of recurrent disease or distant metastases and correlated its diagnostic accuracy with prostate-specific antigen (PSA) levels in prostate cancer patients with biochemical evidence of recurrence. Furthermore, the influences of androgen deprivation therapy (ADT) and its duration on 18 F-FCH PET were assessed in this study. Methods: This prospective study included 250 prostate cancer patients with PSA rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 37 publications
6
64
1
3
Order By: Relevance
“…Castelluci et al reported 11C--choline PET/CT scans indicating metastases in 23% of 605 patients with PSA < 2 ng/mL, and in 18% of 291 patients with PSA < 1.0 ng/mL [15]. This is slightly less than in our study, but almost 25% of the patients in their study received HT at the time of the PET/CT investigation, which is known to affect the sensitivity of choline PET/CT [22]. Also, their study population included more patients with Gleason Score 5--6, with a lower likelihood of metastatic recurrence [7].…”
Section: Discussioncontrasting
confidence: 49%
“…Castelluci et al reported 11C--choline PET/CT scans indicating metastases in 23% of 605 patients with PSA < 2 ng/mL, and in 18% of 291 patients with PSA < 1.0 ng/mL [15]. This is slightly less than in our study, but almost 25% of the patients in their study received HT at the time of the PET/CT investigation, which is known to affect the sensitivity of choline PET/CT [22]. Also, their study population included more patients with Gleason Score 5--6, with a lower likelihood of metastatic recurrence [7].…”
Section: Discussioncontrasting
confidence: 49%
“…One-third of prostate cancer cases were at intermediate-risk (i.e., T1-T2; PSA <20 ng/ mL and GS <8) when diagnosed (Beheshti et al, 2013). These patients may exhibit great variability in outcome as 5-year PSA-based biochemical failure rates range from 9 to 44% following radical prostatectomy (Roberts and Han, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Результаты предыдущих исследований по оценке возможностей ПЭТ / КТ с 11 С-холином в диагностике рецидива РПЖ свидетельствуют об успешном опреде-лении точной его локализации в 36-76 % случаев [17,18,[21][22][23][24][25][26].…”
Section: Introductionunclassified